2020
DOI: 10.1038/s41416-020-0810-1
|View full text |Cite
|
Sign up to set email alerts
|

OX40 and LAG3 are associated with better prognosis in advanced gastric cancer patients treated with anti-programmed death-1 antibody

Abstract: Background Anti-PD-1 monoclonal antibody, nivolumab, has shown efficacy for advanced gastric cancer (AGC). However, the specific immune cell subsets predominantly activated during the period of anti-PD-1 therapy for AGC have not been clarified. Methods Peripheral blood of 30 AGC patients treated with nivolumab was prospectively obtained before the initial and second administrations and at the time of progressive disease (PD). The proportions of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…7d ). Importantly, we also found that these cells positively expressed the T cell exhaustion inhibitory receptors including TIGIT and LAG3 56 , 57 (Fig. 7d ), suggesting that the CD8 + T cells become exhausted after the initial activation phase in OS.…”
Section: Resultsmentioning
confidence: 70%
“…7d ). Importantly, we also found that these cells positively expressed the T cell exhaustion inhibitory receptors including TIGIT and LAG3 56 , 57 (Fig. 7d ), suggesting that the CD8 + T cells become exhausted after the initial activation phase in OS.…”
Section: Resultsmentioning
confidence: 70%
“…Recently, the correlation between the baseline IL-6 and CRP in melanoma treated with immune checkpoint inhibitors (ICIs) or chemotherapy was demonstrated, and higher levels of IL-6 were significantly associated with poor survival 37 . On the other hand, no significant change of systemic levels of IL-6 during ICI treatment has been observed in the studies of melanoma 38 and gastric cancer 39 . In addition, several reports have already shown that CAR is an important prognostic factor for SCC treated with chemoradiotherapy 24 or cytotoxic agents 26 .…”
Section: Discussionmentioning
confidence: 95%
“…Paradoxically, some clinical reports indicated a favorable outcome of cancer patients when LAG-3 expression is observed on tumor-infiltrating immune cells. This is the case for breast cancer [ 80 , 81 ], esophageal adenocarcinoma [ 82 ], and advanced gastric cancer patients treated with PD-1 blocking mAbs [ 83 ]. Here, LAG-3 expression could be considered a marker for T-cell activation.…”
Section: The Prognostic Value Of Lag3mentioning
confidence: 99%